Bohater zbiorowy w twórczości heroicznej Samuela Twardowskiego - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
In this paper the author shows that a crowd in Twardowski’s production becomes a community significant, not only ornamentical. This crowd consists of the nobility and a persons Trom behind the ethos. Twardowski produces a part of the nobility on the structure of presented world and he pays attention to their behaviour: knightly and not knightly. Samuel of Skrzypna shows a struggle on the battle field between antagonistic armies. These armies are presented as an anonymous masses. The poet only occasionally mentions single knight’s unusual contribution. The describes its to open the reading public’s eyes to contribution one and all to the victory. Author of this work also takes up the up-service, so-called camp-followers, their picture in Twardowski’s works. This pictures changes. The camp-followers become conscious of their own power. They see that their actions can influence the results of military campaign. In this paper portrait of Cossacks war skipped. Twardowski like enough the first epic writer notices and appreciates an import of masses in the 17th century literature.